PENGARUH ALOKASI BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA RIAU - Prihastuti, Asepma Hygi (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
as economic growth, infrastructure and government policies. Infrastructure is built by the state through capital expenditure. The purpose of this study is to determine the effect of capital expenditure allocation and economic growth to human development index in Riau district/city 2014-2016. Data processing by path analysis using SPSS version 21. The result of research shows that capital expenditure allocation has direct influence to economic growth in district/city of Riau Province. The allocation of capital expenditure does not have a direct impact on the human development index, while the economic growth directly affects the human development index. And the allocation of capital expenditures indirectly significantly influence the Human Development Index through economic growth.Keywords: allocation of capital expenditure, economic growth, Human Development Index (HDI)